Relationship between Metallothionein and Mercury (Hg) in the Gill Tissue of the Barbonymus altus in the Brantas River Jombang, East Java - Aang Setyawan Anjasmara; Hertika, Asus Maizar Suryanto; Yanuhar, Uun (The Journal of Experimental Life Science, 2023)
Pollution of river waters is most often the result of human activities in managing agricultural land, industry, and transportation. The entry of pollutants such as heavy metal mercury (Hg) into the waters can interfere with the survival of fish waters. Red Bader Fish (Barbonymus altus) can be used as a biomarker in analyzing aquatic environmental conditions in the Brantas River, Jombang, East Java. This study aimed to analyze the relationship between metallothionein and heavy metal mercury in the gill tissue of Barbonymus altus. Sampling was conducted at three stations with three replications from February to March 2022. Data analysis used regression and correlation methods to determine the relationship between metallothionein and metal mercury in gill tissue. The density and intensity of metallothionein in the gill tissue of Barbonymus altus were analyzed using the immunohistochemical method. The mercury (Hg) content in the gill tissue of Barbonymus altus was analyzed using Atomic Absorption Spectroscopy (AAS). The results showed that the metallothionein density at each station included station 1 of 252.52 × 10-6 – 497.79 × 10-6 MT.µm-2, station 2 of 277.78 × 10-6 – 378.78 × 10-6 MT.µm-2, and station 3 of 303.03 × 10-6 – 404.04 × 10-6 MT.µm-2. The relationship between the metallothionein density value and mercury in the gill tissue has a moderate correlation. In contrast, the metallothionein intensity value with mercury in the gill tissue strongly correlated with a significance value of sig < 0.05. The Hg levels in the gill tissue, density, and intensity have significant values at the all three locations based on the real difference test (sig. 0.00).   Keywords: Barbonymus altus, density, intensity, mercury, river.